PENGAWASAN SENJATA INTERNASIONAL DAN PENGURANGAN KEKERASAN - TRI CAHYO UTOMO, TRI CAHYO UTOMO (Politika: Jurnal Ilmu Politik, 2011)
Abstract Arms control, a policy which is intended to limit the production and utilization of weapons, has been known by human beings for centuries. It is required not only to reduce the number of violence but also to increase the quality of peace. Yet, history teaches that arms control do not bring consequence to the decrease of rivalry and conflict among countries automatically. Harshness and war still occur in every part of the world andÂ  seem unavoidable. Key words: arms control, violence, treaty.